2000
DOI: 10.1002/(sici)1099-0690(200005)2000:9<1735::aid-ejoc1735>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The LiClO4-Mediated Synthesis of β-(Dialkylamino) Sulfoxides and β-(Dialkylamino) Sulfones by Addition of α-Lithiated Salts of Sulfoxides and Sulfones to Aldehydes and (Trimethylsilyl)dialkylamines

Abstract: The LiClO4‐mediated one‐pot reaction of aldehydes with (trimethylsilyl)dialkyl amines and the lithium salt of sulfoxides or sulfones, affords the corresponding β‐(dialkylamino) sulfoxides and β‐(dialkylamino) sulfones in high yields. The aminosulfoxidation reaction of aliphatic or aromatic aldehydes lacks diastereoselectivity, but the diastereomeric sulfoxides can be separated by HPLC or column chromatography for further use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…50,[55][56][57] First, it was shown that aromatic and heteroaromatic aldehydes were aminoalkylated by trimethylsilylamines in the presence of lithium perchlorate. [58][59][60][61][62][63] Imines or iminium salts formed in the first step of the reaction were trapped by the corresponding nucleophile to afford corresponding amines 69, 70 (Scheme 41). Later, the approach was modified in order to allow trimethylsilylamines to be generated in situ.…”
Section: Three-component Condensationsmentioning
confidence: 99%
“…50,[55][56][57] First, it was shown that aromatic and heteroaromatic aldehydes were aminoalkylated by trimethylsilylamines in the presence of lithium perchlorate. [58][59][60][61][62][63] Imines or iminium salts formed in the first step of the reaction were trapped by the corresponding nucleophile to afford corresponding amines 69, 70 (Scheme 41). Later, the approach was modified in order to allow trimethylsilylamines to be generated in situ.…”
Section: Three-component Condensationsmentioning
confidence: 99%
“…Cycloaddition reactions between transition-metal 2-alkynyl and η 1 -allyl complexes and unsaturated electrophilic reagents have been studied in detail over the last 30 years . The pioneering works in this area have been done by the groups of Rosenblum, Wojcicki, and Welker. 1c,d The [3 + 2] cycloaddition reactions of η 1 -allyl complexes have been shown to yield transition-metal-substituted heterocyclic as well as carbocyclic five-membered rings which offer alternative approaches to prepare these ring systems, when the metal moiety is subsequently removed from the ring. The reaction of the lithium enolate of the pseudooctahedral complex (η 5 -Cp)Fe(PPh 3 )(CO)COCH 3 with Eschenmoser's iminium salt and the reactions of complex 1 with N -tosylimines, which are activated by Lewis acids such as BF 3 ·OEt 2 , ZnCl 2 , MgBr 2 , SnCl 4 , and TiCl 4 , have been reported in the literature. , As a continuation of our research devoted to the reaction of nucleophiles with iminium salts, , especially in situ generation of iminium ions, herein we report a new and practical entry to a series of interesting nitrogen-containing heterocyclic compounds (Scheme ).
1 Reaction of Complex 1 with Eschenmoser Salt
…”
mentioning
confidence: 99%
“…Hydrolysis of 3 gave the corresponding cyclic hydrogen phosphite (4) 11 . The reaction of both phosphorobromodite (3)/ cyclic hydrogenphosphite (4) with various aldehydes and amines in dry toluene at 50-60°C afforded the title compounds in good yields.…”
Section: Resultsmentioning
confidence: 99%